Modelling the effects of Brexit on the British economy - Patrick Minford; Zheyi Zhu (Cardiff University, Cardiff Business School, 2023)
We estimate the short run effects of Brexit border disruption on the UK economy. We estimate a structural VAR for the UK where Brexit effects are identified by the dates of Brexit events, the referendum and the exit from the single market. We find evidence of short run effects of Brexit: temporary effects on GDP, exports and imports (slightly negative),and on inflation and interest rates (slightly positive). These effects are consistent with modest disruption from introducing a border with the EU- a border due to be made barrier-free and seamless by the UK-EU Trade and Cooperation Agreement. Previous work using other countries as comparators is vulnerable to identification difficulties. We also survey earlier modelling work on the long run effects of evolving policies of free trade, UK-sourced regulation and liberalised immigration. Models of long run trade suggest the emergence of substantial gains.
Keywords: 330; Brexit; impact analysis; VAR model; estimation; Great Britain; Brexit; Wirkungsanalyse; VAR-Modell; Schätzung; Großbritannien